God's last words: reading the English Bible from the Reformation to fundamentalism - Kaṣ, Dāwid Ben-Šāʾûl (Yale University Press, 2004)
Preface: The Biblical reader and the shifting horizon of expectations -- The prehistoric English Bible -- In pursuit of a useful Bible : scriptural politics and the English Civil War -- Cracking the foundations : Biblical criticism and the Newtonian synthesis -- Streamlined Scriptures : the demystification of the Bible -- The occult Bible : aesthetization and the persistence of the supernatural -- Divine copyright and the apotheosis of the author in eighteenth-century England -- Ten little Israelites : counting out the Bible in Victorian England -- Unsuitable paternity : Darwin, anthropology, and the evolutionist Bible -- Conclusion: The end of a world and the beginning of fundamentalism